Skip to content

Commit

Permalink
bump deps (#587)
Browse files Browse the repository at this point in the history
  • Loading branch information
tthsqe12 authored Jul 15, 2022
1 parent cbc04de commit 138eeb1
Show file tree
Hide file tree
Showing 2 changed files with 14 additions and 9 deletions.
8 changes: 4 additions & 4 deletions Project.toml
Original file line number Diff line number Diff line change
Expand Up @@ -18,14 +18,14 @@ lib4ti2_jll = "1493ae25-0f90-5c0e-a06c-8c5077d6d66f"
libsingular_julia_jll = "ae4fbd8f-ecdb-54f8-bbce-35570499b30e"

[compat]
AbstractAlgebra = "0.26.0"
AbstractAlgebra = "0.27.0"
BinaryWrappers = "~0.1.1"
CxxWrap = "0.11, 0.12"
Nemo = "0.31.0"
Nemo = "0.32.0"
RandomExtensions = "0.4.2"
Singular_jll = "~403.1.200"
Singular_jll = "~403.100.100"
julia = "1.6"
libsingular_julia_jll = "~0.24.0"
libsingular_julia_jll = "~0.25.0"

[extras]
Test = "8dfed614-e22c-5e08-85e1-65c5234f0b40"
Expand Down
15 changes: 10 additions & 5 deletions test/caller-test.jl
Original file line number Diff line number Diff line change
Expand Up @@ -171,12 +171,17 @@ end
L = Singular.LibHess.RiemannRochHess(r, f, Any[D, E], "free")

@test length(L[1]) == 5
@test length(findall(P->P== 5*x^2*y^3-5*x*y^4-5*x^2*y^2+10*x*y^3-2*y^4-5*x*y^2+4*y^3-2*y^2, L[1])) == 1
@test length(findall(P->P== 2*x^3*y^2+x^2*y^3-3*x*y^4-2*x^3*y-x^2*y^2+6*x*y^3-3*x*y^2, L[1])) == 1
@test length(findall(P->P== 5*x^3*y^2-5*x*y^4-4*x^3*y+10*x*y^3-5*x*y^2, L[1])) == 1
@test length(findall(P->P== 5*x^4*y-5*x*y^4-x^3*y+10*x*y^3-5*x*y^2, L[1])) == 1
@test length(findall(P->P== x^5+2*x^4*y-3*x*y^4+6*x*y^3-3*x*y^2, L[1])) == 1
@test L[2] == x^5
# The real test here is that the QQ-span of L[1] == the Q-span of the five
# polys below. The weaker ideal equality test is sufficient and is less
# cumbersome to type.
@test equal(Ideal(r, L[1]), Ideal(r,
3*x^5 + x^3*y^2 - 4*x^2*y^3 - x^3*y + 4*x^2*y^2 + 3*y^4 - 6*y^3 + 3*y^2,
5*x^3*y^2 - 5*x^2*y^3 - 2*x^3*y + 5*x^2*y^2,
5*x^4*y - 5*x^3*y^2 + 3*x^3*y,
5*x^5 - 5*x^4*y + 3*x^3*y,
x^5 + 2*x^4*y - 3*x*y^4 + 6*x*y^3 - 3*x*y^2
))

R, (x, y, z) = PolynomialRing(QQ, ["x", "y", "z"])
F = y^2*(y-z)-x^3
Expand Down

0 comments on commit 138eeb1

Please sign in to comment.